Ovarian antral follicle number and the amount of gonadotropin used in ovarian stimulation in polycystic ovarian patients. - Sudek, Hanan L. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Polycystic ovary syndrome is the most common cause of anovulation, and the number of antral follicles is of great importance in determining ovarian reserve, so identification of patients with diminished ovarian reserve help in choosing individualized and well managed ovulation induction protocol. The aim of the study is to find out if the number of ovarian antral follicles could affect the amount of gonadotropins used in ovarian stimulation in polycystic ovarian patients. Patients and methods: Ninty four infertile polycystic ovaries women, attending the infertility clinic at Baghdad teaching hospital, during the period of November 2005 to October 2006, were compared to 62 control group women who have unexplained infertility. After exact history and examination, ultrasound was done to both groups at cycle day 3 for antral follicle counting. Then ovarian stimulation was started with gonadotropins, and another ultrasound was done on cycle day 13 for mature follicles confirmation. Results: Antral follicle number was found to be significantly higher in patients than control groups (9.98 ± 2.09 vs 5.40±2.02). Age was found to be negatively correlated with antral follicle size and number in patient and control groups. After measuring the number of mature follicles at cycle day 13 it was observed that the antral follicle number was correlating positively and significantly with the number of follicles at cycle day 13, but negatively with the amount of gonadotropin used for ovarian stimulation in patients and control groups. Conclusion: Antral follicles number is significantly higher in polycystic ovary patients and they correlate negatively with age. Antral follicle number is a good predictor of the number of gonadotropin ampouls used for ovarian stimulation.